KAJIAN TEMATIK HADIS AHMAD NO 3038: ANALISIS KRITIS ATAS FENOMENA KELALAIAN MANUSIA TERHADAP NIKMAT SEHAT DAN WAKTU LUANG - Muhammad Ramdani; Shilvana Anggun Zaskia (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
This study discusses the prophetic hadith reported in Musnad Ahmad no. 3038 about two blessings that are often neglected by people: health and free time. The research aims to analyze the theological meaning of the hadith and its relevance to contemporary social life. The method used is qualitative library research by examining classical Islamic texts and recent academic studies related to health awareness and time management in Islamic perspective. The results show that health and free time are not merely natural conditions but divine trusts that must be utilized responsibly. Many individuals tend to waste their free time on unproductive activities and neglect their health until illness appears. Such behavior reflects a lack of gratitude and awareness of life purpose. Islam encourages believers to maintain physical and spiritual health, use leisure time for beneficial activities, and improve self-quality through worship, knowledge, and social contribution. Therefore, understanding this hadith is expected to build awareness so that health and leisure become means for achieving meaningful and balanced life in both worldly and spiritual dimensions.